2016
DOI: 10.1515/rgg-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamic Research at the Department of Planetary Geodesy, SRC PAS

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It can be concluded that the statistical properties of distribution of distances between pairs of the stations (vector magnitudes) as a variable depended on varying position of the stations (their temporal displacements) and should re ect the characteristics of the displacements' variability, as discussed by Szczerbowski (2016). So, the positions a displacement vector and linear deformation (apparent strain) are also changing in time.…”
Section: The Datamentioning
confidence: 93%
See 4 more Smart Citations
“…It can be concluded that the statistical properties of distribution of distances between pairs of the stations (vector magnitudes) as a variable depended on varying position of the stations (their temporal displacements) and should re ect the characteristics of the displacements' variability, as discussed by Szczerbowski (2016). So, the positions a displacement vector and linear deformation (apparent strain) are also changing in time.…”
Section: The Datamentioning
confidence: 93%
“…The observations are carried by water tube tiltmeter, and extensometers demonstrated some regularities in deformation parameters in certain periods as a result of tension caused by tectonic stress that is considered as recent tectonic activity of the Sudetes. Many tectonic events in the area of the Sudetes were discussed among others in the studies of Kaczorowski and Wojewoda (2011) and Brzeziński et al (2016).…”
Section: Seismic and Aseismic Deformations Interplaymentioning
confidence: 99%
See 3 more Smart Citations